STUDENTS’ PERCEPTIONS OF IMPLEMENTING PROBLEM-BASED LEARNING WITH BLENDED LEARNING IN EFL ACADEMIC READING - Ismail, Hijril; Edi, Edi (University of Kuningan, 2022)
The study aimed at exploring students’ perception of implementing problem-based learning with blended learning in EFL academic reading. Quantitative and qualitative data were gained by applying a questionnaire and semi-structured interviews. The study occurred at the English Education Program at Muhammadiyah University of Mataram. The respondents involved in this research were thirty-four English foreign language (EFL) students who are joining an academic reading course. The result showed that students have positive perceptions of the use of problem-based learning with blended learning in teaching EFL academic reading. At the same time, the respondents found barriers preventing them from utilizing problem-based learning in teaching EFL academic reading such as requiring sufficient time to complete a topic or find out the solution to a problem, needing additional fees to buy internet quota, and needing prior knowledge in applying problem-based learning. Finally, the finding gained from two types of instruments recommended that PBL with blended learning can be applied in EFL academic reading.